2010
DOI: 10.1186/1758-3284-2-18
|View full text |Cite
|
Sign up to set email alerts
|

Living related hemi-face skin transplant using radial forearm free flap for a xeroderma pigmentosa patient: early outcome

Abstract: IntroductionXeroderma pigmentosa (XP) is a hereditary disease characterized by deficient repair of DNA damage that occurred on exposure of the skin to ultraviolet irradiation. The affected children have a propensity to develop multiple skin cancers mainly in the face and eventually die before the age of 20.HypothesisAllograft replacement of facial skin by a healthy skin from normal person might decrease the incidence of skin cancer development, the number of surgical procedures, and eventually might improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, there was consensus regarding skin-sparing resections and the use of skin grafts from donor areas that were not exposed to the sun and/or were poorly pigmented. 36,46,57,58 No study reported continuous, long-term follow-up to determine the incidence of recurrence or new lesions in the grafts or flaps used. This scientific scenario could be explained by the rarity of xeroderma pigmentosum, making it difficult to perform large randomized clinical trials and meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was consensus regarding skin-sparing resections and the use of skin grafts from donor areas that were not exposed to the sun and/or were poorly pigmented. 36,46,57,58 No study reported continuous, long-term follow-up to determine the incidence of recurrence or new lesions in the grafts or flaps used. This scientific scenario could be explained by the rarity of xeroderma pigmentosum, making it difficult to perform large randomized clinical trials and meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty (80%) of the tumors were on the face, one was on the back and three on the forearms. All wounds were closed primarily or with split grafts Amin et al 46 Living related hemi-face skin transplant using radial forearm free flap for an XP patient: early outcome…”
Section: Case Report El: 4 Medicalmentioning
confidence: 99%
“…The already‐acknowledged disputable cases include the penis transplant, uterus transplant, tongue and cephalocervical flap transplant for cancer patients, and the comcomitant face and double hands transplant . In our opinion, the propriety of the thumb transplant, the palm transplant, and the facial flap transplant for xeroderma pigmentosa patient are also questionable . Clearly, the thumb and palm defects were not important enough to risk lifelong immunosuppression; and the xeroderma pigmentosa patient would die sooner with immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45] In our opinion, the propriety of the thumb transplant, the palm transplant, and the facial flap transplant for xeroderma pigmentosa patient are also questionable. [46][47][48] Clearly, the thumb and palm defects were not important enough to risk lifelong immunosuppression; and the xeroderma pigmentosa patient would die sooner with immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include abdominal wall tissue (for breast reconstruction), 9 omentum (for scalp repair), 10 uterus, 11 and fasciocutaneous radial forearm tissue (for hemifacial reconstruction). 12 Despite successful outcomes, these cases have raised legal and 1245e ethical concerns with respect to living donation in vascularized composite allotransplantation. Specifically, compared to solid organ transplantation, the benefits of live donor allotransplantation are less clear.…”
mentioning
confidence: 99%